2010
DOI: 10.1029/2009jb006833
|View full text |Cite
|
Sign up to set email alerts
|

Rupture modes in laboratory earthquakes: Effect of fault prestress and nucleation conditions

Abstract: [1] Seismic inversions show that earthquake risetimes may be much shorter than the overall rupture duration, indicating that earthquakes may propagate as self-healing, pulse-like ruptures. Several mechanisms for producing pulse-like ruptures have been proposed, including velocity-weakening friction, interaction of dynamic rupture with fault geometry and local heterogeneity, and effect of bimaterial contrast. We present experimental results on rupture mode selection in laboratory earthquakes occurring on fricti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
78
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 39 publications
(91 citation statements)
references
References 56 publications
13
78
0
Order By: Relevance
“…Such frictional behavior, combined with sufficiently low shear prestress, can lead to generation of short-duration self-healing ruptures typically called pulse-like (Refs. [16,[26][27][28]) which may be the rupture process of choice for large earthquakes [29].…”
Section: 2mentioning
confidence: 99%
“…Such frictional behavior, combined with sufficiently low shear prestress, can lead to generation of short-duration self-healing ruptures typically called pulse-like (Refs. [16,[26][27][28]) which may be the rupture process of choice for large earthquakes [29].…”
Section: 2mentioning
confidence: 99%
“…To understand the mechanism of catastrophic rupture like earthquake and investigate the way to forecast the catastrophe, numerous rock experiments were conducted by many researchers [33][34][35][36][37]. It was claimed that these model earthquakes should provide a better understanding of the mechanisms that may lead to large seismic events in the real world [35][36].…”
Section: Introductionmentioning
confidence: 99%
“…In the laboratory earthquakes generated by Lu (2009) and Lu et al (2010), rise time (measured in μs) was found to be linearly correlated with slip (measured in μm), as shown in Figure 2. The rise times shown are the basal widths of the best-fitting isosceles triangles to the slip velocity-time functions measured in the laboratory.…”
Section: Slip Velocity-time Functionmentioning
confidence: 92%
“…In addition to field observations and theoretical models, laboratory earthquakes have yielded important insights into the fault rupture process. Stable pulse-like ruptures have been realized in the laboratory under controlled conditions (Rosakis et al, 1999(Rosakis et al, , 2007Lu, 2009;Lu et al, 2010;Mello et al, 2010). Both sub-Rayleigh and supershear ruptures have been realized.…”
Section: Rupture Speed Distributionmentioning
confidence: 99%